Dampak Information and Communication Technology (ICT) Terhadap Produktivitas dan Pertumbuhan Ekonomi di Indonesia - Yulianti; Anward, Ryan Juminta (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aimed to explain the impact of Information and Communication Technology (ICT) on productivity and economic growth in Indonesia. The data used in this study are sourced from the World Bank and Federal Reserve financial data. The analysis in this study uses the Vector Autoregression/ Vector Error Correction Model (VAR/ VECM) technique to identify the impact and influence of ICT on productivity and economic growth in Indonesia in the short and long term. The results of this study indicate a long-term relationship between productivity based on total factor productivity (TFP) data and economic growth with other variables used in this research. In the research results, Fixed Broadband Subscription (FBS) and Internet Users (INT) have a significant and positive impact on economic productivity in the long term. Still, they are not substantial in the short time. Then, Fixed Broadband Subscription (FBS) and ICT Goods Export (ICTEXP) have a significant and positive impact on economic growth in the long term but are also insignificant in the short time.